2006
DOI: 10.2151/jmsj.84.477
|View full text |Cite
|
Sign up to set email alerts
|

Error Characteristics of GPS Retrieved Refractivity Using a Simulation Study

Abstract: A simulation study was designed to investigate the error characteristics of retrieved local refractivity arising only from the assumption of spherical symmetry. The convergence of error estimation with respect to different horizontal resolutions was examined, and a resolution higher than 30 km was found to be reasonable for this simulation study.Two cases, one in summer 1997 and the other in winter 1998, were used to study errors of retrieved local refractivity. The error can reach 10 units in the lower tropos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…1b), ex cept be low 6 km where a larger dif fer ence arises pos si bly due to the data scar city for CHAMP at lower al ti tudes. The ob serva tion er ror pro duced by lo cal op er a tor shows an ap prox imately ex po nen tial de cay with a max i mum in the low est level of about 3%, which is con sis tent with the es ti mate of Chen et al (2006) us ing a 50-km res o lu tion. The nonlocal op er a tor pro duces smaller er rors even at the low est height, and the er rors are gen er ally less than 1% at all the lev els and 0.5% above 6 km.…”
Section: Ob Ser Va Tion Er Rorsmentioning
confidence: 55%
See 1 more Smart Citation
“…1b), ex cept be low 6 km where a larger dif fer ence arises pos si bly due to the data scar city for CHAMP at lower al ti tudes. The ob serva tion er ror pro duced by lo cal op er a tor shows an ap prox imately ex po nen tial de cay with a max i mum in the low est level of about 3%, which is con sis tent with the es ti mate of Chen et al (2006) us ing a 50-km res o lu tion. The nonlocal op er a tor pro duces smaller er rors even at the low est height, and the er rors are gen er ally less than 1% at all the lev els and 0.5% above 6 km.…”
Section: Ob Ser Va Tion Er Rorsmentioning
confidence: 55%
“…Af ter ap ply ing the Abel inversion for bend ing an gles, GPS RO refractivity pro files can be ob tained at an occultation point as an in ter me di ate prod uct with pre sumed lo cal spher i cal sym me try. There are sev eral im pact stud ies us ing GPS RO refractivity soundings (Kuo et al 2004Huang et al 2005;Chen et al 2006;Cucurull et al 2006). For ex am ple, Huang et al (2005) assim i lated sev eral GPS RO refractivity soundings into the fifth-gen er a tion Penn syl va nia State Uni ver sity Na tional Cen ter for At mo spheric Re search Mesoscale Model (MM5) with a three-di men sional variational data as sim i la tion system (3DVAR) and showed that both track ing and ac cu mulated rain fall pre dic tions were im proved in sim u lat ing two ty phoons which struck Tai wan, Nari (2001) and Nakri (2002).…”
Section: Introductionmentioning
confidence: 99%
“…1, covering latitudes from about 108S to 508N and longitudes from 808 to 1608E, with a model top of 50 hPa (31 model vertical levels) with varied vertical resolution. The horizontal resolution of 45 km in this study should be appropriate for the error estimation according to Chen et al (2006). They computed the innovation using the fifth-generation Pennsylvania State University-National Center for Atmospheric Research (NCAR) Mesoscale Model (MM5) with different horizontal resolutions and found that the representativeness error from 30-km resolution is compatible with that of 10-km resolution.…”
Section: E Model Settings and Calculation Stepsmentioning
confidence: 94%
“…The ray tracing technique has been applied to assess the impact of data assimilation (Zou et al 1999;Liu and Zou 2003;Zhang et al 2004) and support the RO observation (Lusignan et al 1969;Beyerle and Hocke 2001;Yeh et al 2012). It also has been applied to develop retrieval methods or estimate retrieval errors (Zou et al 2002;Jensen et al 2003;Chen et al 2006;Li and Kiang 2011;Mannucci et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose the earth's atmosphere is assumed to be nonspherically symmetric. The analytic atmosphere models, such as the National Centers for Environmental Prediction (NCEP) and the European Centre for Medium-Range Weather Forecasts (ECMWF), are used in the ray tracing operator (Zou et al 1999(Zou et al , 2002Liu and Zou 2003;von Engeln et al 2003;Zhang et al 2004;Chen et al 2006) with the elliptical earth. Nevertheless, the initial and end points of the signal in the former ray tracing operators are not considered to correspond to the position of the GPS and LEO satellites.…”
Section: Introductionmentioning
confidence: 99%